A Study on the Conservation Programs for Tigers: Enhancing Tiger Conservation through Conservation Landscapes (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Over the past 150 years the tiger range has collapsed by more than 93, and the wild tiger population has declined to less than 3,500 animals. The precipitous decline is attributed in part to poaching, but also to extensive habitat loss and fragmentation. The remaining tigers live as isolated populations confined to protected areas, scattered across the vast range, from India to Indonesia and north to the Russian Far East. Many of the protected areas are, however, too small to sustain viable populations and the natural ecology and behavior of tigers. In response, conservation biologists have proposed a new paradigm for conserving tigers the creation of conservation landscapes, where proximate protected areas can be linked with habitat corridors that can facilitate dispersal movement and maintain ecological and genetic connectivity. Managing the tiger populations as larger, connected meta-populations can increase the ecological, demographic, and genetic viability of tiger populations, and the probability of long term persistence.